Performance of amidoxime-modified poly(acrylonitrile- Co-acrylic acid) for removal of boron in aqueous solution - Lau, Kia Li (2019)
Boron is an essential micronutrient for plants, humans and animals, which is also an important component in various industries. Along with the wide spread of boron application, more boron waste pollutes the water sources, and leads to a series of environment and health problems. Adsorption is the most efficient technique among many boron removal technologies; which can treat solutions containing a very low concentration of boron.